Oziroë imbricata: a new bulbous species of Asparagaceae (Scilloideae: Oziroëeae) endemic to the Atacama Desert, Chile - Cádiz-Véliz, Arón; Casale, Jean-François (Phytotaxa, 2026)
The subfamily Scilloideae (Asparagaceae) is represented in South America exclusively by the bulbous genus Oziroë, the sister lineage to the remainder of the subfamily, currently comprising five recognized species distributed across arid, semiarid, and Mediterranean ecosystems. In this study, we describe Oziroë imbricata, a new species endemic to the coastal desert of the Atacama Region in northern Chile. The species was discovered during a “Desierto Florido” event on inland plains south of the Totoral River (27°S, 70°W), in a fog-influenced xerophytic scrubland. Oziroë imbricata is morphologically remarkable within the genus for its large, strongly reflexed, canaliculate tepals and filaments overlapping one another and forming a conspicuous tube-like structure around the ovary and style, a unique combination of traits in the genus Oziroë. We provide a detailed morphological description supported by photographs, illustrations, a distribution map, and a comparative table contrasting the new species with its closest morphological relatives, O. biflora and O. arida. Currently, the species is known from a narrow coastal belt between Totoral and the Huasco River, at elevations of ca. 90–450 m a.s.l., where it inhabits open desert scrub, including populations recorded along the northwestern boundary of Llanos de Challe National Park. Using GeoCAT, we estimate an Extent of Occurrence (EOO) of 715 km² and an Area of Occupancy (AOO) of 28 km². We propose the category Vulnerable (VU) under IUCN criterion B2ab(iii), based on its small AOO, few known localities, and multiple anthropogenic threats, including mining, photovoltaic development, and unregulated grazing. An updated key to the South American species of Oziroë is also provided.